Incorporation of Nucleoside Probes Opposite O6‐Methylguanine by Sulfolobus solfataricus DNA Polymerase Dpo4: Importance of Hydrogen Bonding. Issue 13 (19th August 2013) - Stornetta, Alessia; Angelov, Todor; Guengerich, F. Peter; Sturla, Shana J.
Abstract O 6‐Methylguanine (O6‐MeG) is a mutagenic DNA lesion, arising from the action of methylating agents on guanine (G) in DNA. Dpo4, an archaeal low‐fidelity Y‐family DNA polymerase involved in translesion DNA synthesis (TLS), is a model for studying how human Y‐family polymerases bypass DNA adducts. Previous work showed that Dpo4‐mediated dTTP incorporation is favored opposite O6‐MeG rather than opposite G. However, factors influencing the preference of Dpo4 to incorporate dTTP opposite O6‐MeG are not fully defined. In this study, we investigated the influence of structural features of incoming dNTPs on their enzymatic incorporation opposite O6‐MeG in a DNA template. To this end, we utilized a new fluorescence‐based primer extension assay to evaluate the incorporation efficiency of a panel of synthetic dNTPs opposite G or O6‐MeG by Dpo4. In single‐dNTP primer extension studies, the synthetic dNTPs were preferentially incorporated opposite G, relative to O6‐MeG. Moreover, pyrimidine‐based dNTPs were generally better incorporated than purine‐based syn‐conformation dNTPs. The results suggest that hydrophobicity of the incoming dNTP appears to have little influence on the process of nucleotide selection by Dpo4, with hydrogen bonding capacity being a major influence. Additionally, modifications at the C2‐position of dCTP increase the selectivity for incorporation opposite O6‐MeG without a significant loss of efficiency.